Association Between Circular RNAs and Intracranial Aneurysm Rupture Under the Synergistic Effect of Individual Environmental Factors - Huang, Qing; Sun, Yi; Huang, Qiuyu; Zeng, Yile; Lin, Shaowei; Huang, Shuna; Cai, Yingying; Xu, Xingyan; Kang, Dezhi; Li, Huangyuan; Wu, Siying (Frontiers in Neurology, 2021)
Introduction: To study the association between specific circular RNAs and rupture of intracranial aneurysm. To explore its clinical diagnostic significance and synergistic effects with individual environmental influencing factors. Methods 347 cases and controls were included in this study. Multivariate analysis was used to explore the main individual environmental factors. Intracranial aneurysm rupture related circular RNAs screened based on sequencing was verified in peripheral blood by PCR. ROC curve, logistic regression model and fork analysis were used to study the association, diagnostic values and synergistic effects of circular RNA with intracranial aneurysms and individual environmental factors. Results Smoking, hair dyeing, sitting time ≥6 h/day, single animal oil intake and hypertension are the main risk factors for intracranial aneurysm rupture; People with higher education, sleeping time ≥7 h/day, tea drinking, diabetes, higher levels of (hemoglobin, low density lipoprotein, serum calcium and apolipoprotein-A1) have a low risk of intracranial aneurysm rupture. Hsa_circ_0008433 and hsa_circ_0001946 are closely related to intracranial aneurysm rupture and have certain clinical diagnostic significance (AUC=0.726; 95% CI: 0.668~0.784). Hsa_circ_0008433 (OR=0.497, 95% CI: 0.338~0.731), hsa_circ_0001946 (OR=0.682, 95% CI: 0.509~0.914) were independent epigenetic factors affecting intracranial aneurysm rupture, and have a multiplicative interaction with age (OR=3.052, 95% CI: 1.006~9.258). Conclusions Low expressions of hsa_circ_0008433 and hsa_circ_0001946 are risk factors for intracranial aneurysms rupture and have good clinical diagnostic value. There was a multiplicative interaction between epigenetic score and age. The older and the higher the epigenetic score was, the more likely to have intracranial aneurysm rupture.